A case report of adjustment for tip of the totally implantable venous-access ports in the neck after placement through the veins of right upper limb (1例经右上臂植入输液港尖端颈内异位调整的经验总结) - CHEN Yao (陈垚); DENG Anmeng (邓安梦); TAN Jiali (谭佳丽); CHEN Yingchun (陈迎春) (中西医结合护理)
This paper summarized the influence factors and adjustment methods for dislocation of tip of the totally implantable venous-access ports(TIVAPs)in the jugular vein after placement through the veins of right upper limb and related adjustment method. Factors causing the dislocation of TIVAP tip included inappropriate placement, lack of experience and issues associated with internal jugular vein lumen. It is suggested that improvement measures such as changing body position, adopting compression repair, modifying placement method, intracavitary electrocardiogram and vascular intervention should be carried out to prevent the dislocation of tip of TIVAPs in the jugular vein. (本文总结了导致经右上臂植入输液港发生尖端颈内异位的相关因素以及调整处理方法。导致异位的因素有操作不当、操作员经验缺乏、管腔自身因素等, 置管时如中心静脉导管发生颈内异位则可以采用体位改良法、压迫法、改良送管法以及腔内心电图技术、血管介入等方法来预防导管颈内静脉异位。)